Resilience Among Parents of Adolescents With Type 1 Diabetes: Associated With Fewer Parental Depressive Symptoms and Better Pediatric Glycemic Control - Luo, Dan; Wang, Yubing; Cai, Xue; Li, Ruxue; Li, Mingzi; Liu, Haiyan; Xu, Jingjing (Frontiers in Psychiatry, 2022)
Background: Resilience plays a significant role in resisting negative moods and improving health outcomes. Little research exists regarding resilience among the parents of adolescents with Type 1 diabetes. Objective: To investigate (a) the level of resilience among parents of adolescents with Type 1 diabetes; and (b) the correlations that parental resilience has with parental depressive symptoms, parental diabetes distress, and paediatric glycaemic control. Methods: This cross-sectional study recruited 224 dyads, consisting of adolescents with Type 1 diabetes and their parents, from two hospitals. The parents completed questionnaires. The 10-item Connor-Davidson Resilience Scale measured resilience; the Problem Areas in Diabetes Survey-Parent Revised version measured diabetes distress; the Patient Health Questionnaire-9 measured depressive symptoms. Standard glycated haemoglobin tests were performed on the adolescents. Results: Approximately 30% of parents had severe depressive symptoms and 52.7% of them exceeded the criterion score for high resilience. Parental resilience was significantly negatively associated with parental depressive symptoms and diabetes distress. Parents from the high-resilience group reported fewer negative moods than those from the low-resilience group. In multivariate regressions, greater parental resilience consistently related to better paediatric glycaemic control beyond parental psychological risk factors. Conclusions: This study highlights the importance of parental resilience for parental mental health and glycaemic control among adolescents with Type 1 diabetes. Appropriate resilience support programme might be developed for parents, especially for those existing significant negative moods.